Analisis Proses Perizinan Klinik Swasta Berbasis Online Single Submission (OSS) Oleh Dinas Kesehatan Kabupaten Karawang - Simanjuntak, Esther Cristianti; Hermana, Cecep (Jurnal Ilmiah Wahana Pendidikan, 2023)
Clinic licensing is an important part of public service. Permenkes 9 of 2014 concerning Clinics is a means of control related to . After the visitation process is complete, the Health Office will issue a Standard 3 Certificate issued by the Health Office and then the clinic verification process continues on the DPMPTSP website. Prior to the OSS agency, the clinic approval process in Indonesia often involved several different government agencies, such as the Food and Drug Administration (BPOM), the Ministry of Health and the local Health Office...Each agency has different requirements and procedures, which can be time-consuming and costly for clinic owners...OSS allows clinic owners to enter information and attach the required documents to a single application, which is then reviewed by the relevant authorities...This licensing process, which gives birth to a standard certificate, protects clinics that want to build buildings and business licenses so that if there are problems, they can show the standard certificate as proof that the clinic is licensed.